(untitled) (Castilla. Estudios de Literatura, 2025)
This is a review of the essay Ciencia ficción capitalista in which the author, Michel Nieva, explains the connection, since its first texts, between science-fiction literature and technological progress, and the projection of the future towards which we want to progress.